Determinants of Bank Acquisitions in ASEAN - Ng, Seok Lee (2013)
A considerable number of acquisitions have taken place in the ASEAN banking industry from the 1997 Asian financial crisis onwards. The trend raises the question as to what ex-ante factors motivate the involvement of banks in acquisitions, as existing literature indicates inconclusive benefits from M&As. As such, the study examines the determinants of acquisitions for 47 acquired banks and 33 acquiring banks in ASEAN from 2003 to 2011. Three logistic regressions are employed to identify the bank-specific and country-specific determinants of bank acquisitions. The results indicate that growth is an important determinant of bank acquisitions. Banks with higher growths are more likely to engage in acquisitions. Furthermore, acquired banks tend to have poorer performance in terms of lower profitability. Thus, the evidences support the inefficient management hypothesis and growth-resource hypothesis. The division of the sample into sub-samples reflects significant changes in the determinants of the likelihood of being acquired over different time periods. In the normal period prior to the financial crises, acquired banks are also found to have greater loan activities. Interestingly, asset quality and liquidity played important roles in determining the likelihood of being acquired in the period after the onset of the global financial crisis and the European sovereign debt crisis. On the other hand, acquiring banks are characterised by high growth. Larger banks with higher growth and greater profitability are also more likely to engage in acquisitions as acquiring banks rather than as acquired banks. Besides bank-specific determinants, external factors also drive bank acquisitions in ASEAN. This is evidenced by the significant influence of a country‟s economic freedom on the likelihood of engaging in acquisitions.